Obtención de un material refractario a partir de un material particulado con alto contenido de oxido (2014)
In Colombia most companies where aluminum ingots are made, not taken into account the waste generated in the process of melting the raw material; these wastes are generated in large part by the flux which allows the precipitation of impurities, these carry a lot of dross aluminum (Al dross) that is stored or discarded without any use, however this scum when being processed it is a great source for use in different materials due to its good properties. Salt slag is a residue generated by the secondary aluminum processing. According to the immediate operations performed for download and cooling smelters have two types of salt slags: loose and compact. According to the European Waste Catalogue, issued in Basel, salt processing of secondary aluminum slags are classified as hazardous waste due to its possible reaction with water or humidity, resulting in the generation of gases or leaching of toxic elements in soils and aquifers. However the aluminum salt slag waste represent a major potential recovery, as the recovery of by-products such as aluminum and other metal products such as metal oxides and melting salts , potassium and magnesium is possible.